Prophetic Political Meritocracy: Re-evaluating Prophet Muhammad’s Governance Framework for Contemporary Political Leadership - Muhammad Akhir Harahap; Khoirotun Nisa Aulia; Muhammad Fathi Aswan; Anggi Sahputra; Salman Faris Dalimunthe (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to examine the prophetic political meritocracy model in the leadership of Prophet Muhammad (peace be upon him) and to evaluate its relevance as a governance framework for contemporary political leadership. The study employs a qualitative approach using a library research design. The findings reveal that Prophetic political meritocracy is constructed through the integration of four prophetic virtues (ṣidq, amānah, tablīgh, and faṭānah) with a governance system that emphasizes justice, deliberation (shūrā), public accountability, the rule of law, social inclusiveness, and the appointment of public officials based on competence and integrity rather than kinship, patronage, or social status. This model demonstrates that political legitimacy in the governance of Prophet Muhammad (peace be upon him) was established through a balance between professional competence and moral responsibility in the exercise of public authority. The study proposes prophetic political meritocracy as a conceptual framework for political leadership that integrates ethical, institutional, and professional dimensions. It thereby contributes to enriching the discourse on Islamic political thought while offering an alternative perspective for reforming contemporary public governance toward greater justice, accountability, transparency, and the promotion of the public good.